Implikasi Dispensasi Kawin Sebagai Penyebab Tingginya Resiko Angka Perceraian Bagi Anak Akibat Perkawinan Paksa Berdasarkan Hak-Hak Perempuan - Prabananda PY, Putu Anjali Gita; Hartati, Endah (Wajah Hukum, 2025)
The purpose of this research is to analyze the impact of marriage dispensation on children and the legal recovery steps related to it. Marriage dispensation regulated in Article 7 paragraph (2) of Law No. 16 of 2019 triggers various problems, especially the increase in divorce rates and violations of women's rights. This policy is considered discriminatory because it opens up opportunities for forced marriages for girls who are not yet mature physically, mentally, or economically. This research uses normative juridical methods and a conceptual approach to analyze the impact of marriage dispensation and legal recovery measures. The results indicate the need for judicial review and legislative review to tighten regulations, prevent abuse, and protect the rights of children and women. This is expected to encourage the revision of legal norms to better align with the principles of justice and child protection.